Enhancing the Quality of Life of Older Persons with and Without a Disability through Adapted Physical Activity Across Europe (Baltic Journal of Sport and Health Sciences, 2018)
Research data estimate that by the end of 2040 the severely impaired adults will be 6.5% of the total population inEurope, or 24.5 million people. Today 7.5% of the total European population is 75 years old and more. In 30 yearsthis percentage will rise to 14.4%. Ageing is a process that often affects and restricts the people who are growing old,on physical, psychological and social level. As older adults are the fastest growing group, attention needs to be givento them as a special population in the area of exercise and sport. The review article aims to present research data inintervention and prevention of disease and disability in older persons through adapted physical activity as well asanalyze some theoretical models for changing physical inactivity into an active lifestyle in older people. As analysisof literature showed, all older adults at all ages should be encouraged to move more, and increase aspects of physicalactivity in their lives; this may be balance and posture, strength training, or moderate or / and vigorous intensityactivities, but it is important to maintain a regular habit throughout older years. Specific targets should be tailoredto the capacity, the motivation, expectations and confidence in older individuals, in all societies and demographicgroups. The research data about the benefits of physical activity are clear and convincing. Till now there is a need toact and find the best strategy and policy to realize this active lifestyle leading to a better health and more well-being.Keywords: ageing, disability, adapted physical activity, thematic network.